Persepsi Calon Guru Bahasa Indonesia yang Berasal dari Kampus UIN Jakarta terhadap Kurikulum Merdeka - Rini Andriani; Hindun Hindun (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Merdeka Curriculum is a curriculum that will be used nationally starting in 2024. This research was conducted to find out how much knowledge students of the Indonesian Language and Literature Education study program from UIN Jakarta have regarding the Merdeka Curriculum. The method used in this research is descriptive qualitative. The data from this research were obtained from the answers of Indonesian Language and Literature Education students in semester 3 class B to questions on Google Forms related to the Independent Curriculum chosen by the researcher. Of the 35 respondents, 10 respondents were classified as already knowing more about the Independent Curriculum information, while the other 25 respondents' level of knowledge regarding the Independent Curriculum information was still quite low.